Fatty acid, the lipid classes, phospholipid composition of the mussels \(Beguina semiorbiculata\) from Nam Du and Phu Quoc islands, Kien Giang province, Vietnam - Dang Thi, Phuong Ly; Dang Thi, Minh Tuyet; Dao Thi, Kim Dung; Dau, Van Thao; Pham, Quoc Long (Vietnam Journal of Marine Science and Technology, 2022)
This study aims to analyze compositions of lipid classes, phospholipid subclasses and fatty acids in two mussels, Beguina semiorbiculata, harvested from Nam Du and Phu Quoc islands, Kien Giang province. The obtained results indicated that the total lipid contents of the B. semiorbiculata harvested in Nam Du and Phu Quoc islands were 0.48% and 0.63% of wet weight, respectively, and contained six classes: Hydrocarbon and wax (HW), triacylglycerol (TAG), free fatty acids (FFA), sterol (ST), polar lipid (PoL), and monoalkyl diacylglycerol (MADAG). Two main classes in the total lipid content of two studied mussels were triacylglycerol (TG) (38.22% and 41.27%) and polar lipid (PL) (27.02% and 30.46%). PL of both muselles consited of five types: Phosphatidylethalnolamine (PE), phosphatidylcholine (PC), phosphatidylserine (PS), phosphatidylinositol (PI) and ceramide aminoethylphosphonate (CAEP) in which phosphatidylethanolamine (PE) (34.34% and 37.08%) and phosphatidylcholine (PC) (26.32% and 26.54%) were dominated. The content of polyunsaturated fatty acids (34.41%) in the total lipid of B. semiorbiculata collected in Phu Quoc was higher than that (26.36%) in Nam Du. The content of n-3 and n-6 fatty acids (20:4n-6, 20:5n-3, 22:6n-3) was high in the composition of fatty acids of both mussels.